Analyzing The Impact of Public Debt and Capital Expenditure ‎on Gross Domestic Product (GDP): A Case Study of The Jordanian Economy (2008-2024)‎ - Shadeed , Assoc. Prof. Dr. Mahdi Khaleel; Hassan, Asst. Lect. Kareem Obayes; Alaallah, Assoc. Prof Dr. Abduljasim Abbas; Mahan, Mr. Abbas Khalid (International Journal of Accounting and Economics Studies, 2025)
This study investigates how domestic and external public debt, together with capital expenditure, have shaped the trajectory of Jordan’s ‎gross domestic product (GDP) from 2008 to 2024. Considering Jordan’s ongoing exposure to external shocks and deep-seated structural ‎vulnerabilities, the analysis highlights the pivotal role of fiscal policy in steering macroeconomic outcomes and fostering long-term stability, ‎particularly during periods of pronounced economic volatility.‎As a relatively small and structurally open economy, Jordan remains highly dependent on imported energy, making it especially susceptible ‎to both domestic and external shocks. Elevated public debt—measured both in absolute terms and as a share of GDP—further amplifies the ‎country’s vulnerability to regional geopolitical and economic instability. Nevertheless, the government has pursued a series of policy ‎reforms designed to improve the effectiveness of public debt management and capital expenditure in supporting sustainable growth.‎In addition, public debt management and capital expenditure effectiveness are closely linked to government accounting practices and fiscal ‎transparency. Proper classification and monitoring of debt instruments can reduce fiscal risks and support long-term macroeconomic stability.‎The econometric analysis, conducted using EViews (2009), provides evidence of cointegration among the variables. This indicates that, over ‎time, short-term fluctuations in public debt and capital investment can contribute to correcting long-term imbalances in real GDP.
Keywords: Public Debt; Capital Expenditure; Gross Domestic Product (GDP).